2017
DOI: 10.1186/s13568-016-0307-8
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel glutamate dehydrogenase from Geotrichum candidum with higher alcohol and amino acid activity

Abstract: Crude enzyme from Geotrichum candidum S12 exhibited high activity towards hexanol at pH 4.0, distinguishing it from currently known enzymes. To identify the dominant enzyme contributing to this activity, the crude enzyme extract was separated into different fractions by ammonium sulfate precipitation, MonoQ anion-exchange chromatography, and Sephacryl S-200 gel filtration chromatography. Afraction with high activity towards hexanol at pH 4.0 was obtained, exhibiting 38-fold improved purity and a specific activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…are yeast‐like fungi widely used in biotechnology, for example in cheese making, in the biodegradation of oil stains and decomposition of cellulose (Hyde et al, 2019). Zhu et al, (2017) showed significant degradation of higher alcohols, such as hexanol and isoamyl alcohol, at low pH by glutamate dehydrogenase produced by the species G. candidum .…”
Section: Discussionmentioning
confidence: 99%
“…are yeast‐like fungi widely used in biotechnology, for example in cheese making, in the biodegradation of oil stains and decomposition of cellulose (Hyde et al, 2019). Zhu et al, (2017) showed significant degradation of higher alcohols, such as hexanol and isoamyl alcohol, at low pH by glutamate dehydrogenase produced by the species G. candidum .…”
Section: Discussionmentioning
confidence: 99%
“…G. candidum S12 was shown to produce a novel glutamate dehydrogenase, which was highly active against glutamate, hexanol, α-ketoglutarate, and isoamyl alcohol (Km values of 41.74, 4.01, 20.37, and 19.37 mM, respectively) [ 144 ]. The catalytic activity against hexanol was enhanced by the addition of ADP, K + , Fe 2+ , and Zn 2+ and reduced by EDTA, Mn 2+ , Pb 2+ , ATP, and DTT.…”
Section: Production Of Enzymes With Industrial Interestmentioning
confidence: 99%
“…In the same manner as monovalent, divalent cations can be both activators and inhibitors of NADP + -glutamate dehydrogenase activity in microorganisms [16,17]. Geotrichum candidum S12 glutamate dehydrogenase is unique, as it is characterized by substrate specificity for glutamate, 2-oxoglutarate, hexanol, and isoamil alcohol (3-methyl 1-butanol) [17].…”
Section: Abstract: Acinetobacter Calcoaceticus Imv B-7241 Surfactants Potassium and Sodium Cations Biological Activity Biosynthesismentioning
confidence: 99%
“…In the same manner as monovalent, divalent cations can be both activators and inhibitors of NADP + -glutamate dehydrogenase activity in microorganisms [16,17]. Geotrichum candidum S12 glutamate dehydrogenase is unique, as it is characterized by substrate specificity for glutamate, 2-oxoglutarate, hexanol, and isoamil alcohol (3-methyl 1-butanol) [17]. In the presence of adenosine diphosphoric acid, Fe 2+ , K + , and Zn 2+ , an increase in enzymatic activity relative to hexanol was observed, and in the presence of EDTA, Mn 2+ , and adenosine triphosphoric acid, its inhibition was observed.…”
Section: Abstract: Acinetobacter Calcoaceticus Imv B-7241 Surfactants Potassium and Sodium Cations Biological Activity Biosynthesismentioning
confidence: 99%